Linguistic Globalization and Youth Identity: The Role of English Loanwords in Ethiopian Digital Communication - Anna Kowalska (Britain International for Academic Research (BIAR) Publisher, 2010)
Linguistic globalization has accelerated the diffusion of English vocabulary across multilingual societies. In Ethiopia, English loanwords increasingly appear in youth digital communication, particularly on social media and messaging platforms. This study examines the sociocultural meanings associated with English loanwords among Ethiopian youth and explores how these linguistic choices contribute to identity construction in digital environments. A survey-based quantitative approach was used to gather responses from 410 high school and university students. Participants evaluated their attitudes toward English loanwords using Likert-scale statements related to language identity, modernity, and cultural preservation. Factor analysis and regression techniques were used to analyze the data. The study reveals that English loanwords are widely perceived as symbols of modern identity and global belonging. The majority of participants expressed positive attitudes toward integrating English vocabulary into digital communication while maintaining respect for their native languages. Three attitudinal dimensions Prestige, Integration, and Purism accounted for most of the variance in responses. English loanwords serve not only as communicative tools but also as markers of social identity and global orientation among Ethiopian youth. Language educators and policymakers should recognize digital multilingualism as part of evolving linguistic identities and incorporate these realities into contemporary language education strategies.